Using blockchain technology for transparency in mining: a strategy to reduce corruption and increase accountability - Chipongue, Lizandro Abel Sicato; Caetano, Sandro António Buaza; Barros, António André Chivanga (Brazilian Journal of Science, 2025)
The application of blockchain technology and the implementation of synthetic diamond production represent innovative strategies to transform the mineral resources sector in Angola, with a specific focus on the province of Lunda Sul, where the Catoca mine is located. Blockchain technology aims to improve the governance model and promote greater transparency and traceability in mining operations, a factor that contributes to the mitigation of corrupt practices and the strengthening of corporate responsibility. In addition, the production of synthetic diamonds emerges as a sustainable alternative, capable of reducing the environmental impact associated with traditional mining, and at the same time increasing the competitiveness of the sector in the global market. To support this work, an exploratory and explanatory methodology was adopted, including interviews with key stakeholders, such as two mining companies and the Department of Mines at the Faculty of Engineering of Agostinho Neto University. The referenced interviews enabled a detailed analysis of the current challenges of the sector and the opportunities related to the integration of disruptive technologies, such as blockchain technology, and sustainable practices, such as diamond synthesis. Therefore, the combination of such approaches can transform the Angolan mineral sector, aligning it with contemporary demands for transparency, sustainability, and operational efficiency.